Sosialisasi Olahraga Kesehatan Masyarakat di Madrasah Aliyah Al Muhtadin Arso VI Kabupaten Keerom dalam Upaya Meningkatkan Derajat Kesehatan - Astini Asri; Ipa Sari Kardi; Ansar CS (Lembaga Pengembangan Kinerja Dosen, 2025)
The lack of physical activity levels at school is one of the factors causing the low degree of student health. Based on this problem, the purpose of implementing community service with the socialization method of health sports is to improve the health status of students at Madrasah Aliyah Al Muhtadin Arso VI Keerom Regency. Partners in this community service are students of Madrasah Aliyah Al Muhtadin Arso VI Keerom Regency, totaling 30 students. One day of socialization and filling out the Global Physical Activity Questionnaire (GPAQ) questionnaire with a strong reliability value of 0.67 to 0.73. Through socialization and measurement of physical activity levels, it was found that students were dominant in the moderate category (76.67%). The community service team hopes that after the socialization of health sports, students can be motivated to exercise and do physical activity both at school and in the community